High Prevalence of Soil-Transmitted Helminths Without Concomitant Anemia: A Cross-Sectional Study of Children in an Indonesian Urban Waste Disposal Site - Ka’bah; Risma Yuliana (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Soil-transmitted helminth (STH) infections are a dominant cause of morbidity, particularly anemia, in pediatric populations in low-resource settings. Children residing in urban waste disposal sites (